Uma solução da equação difusão-advecção com o termo contragradiente - Pantoja, Pedro Henrique Bonfim (2014)
In this paper presents a solution to the advection-diffusion equation considering the term is an additional term countergradient. This additional term contains information asymmetry, Lagrangian time scale and vertical turbulent velocity. The solution of the equation was obtained by using the technique of Laplace transform, considering the planetary boundary layer (PBL) as a multilayer system. The turbulent parameters were derived from statistical distribution theory Taylor, combined with the theory of similarity. Hence, Simulations for different values of asymmetry, which allowed to obtain a concentration of contaminants at different heights in a convective boundary layer is displayed. The evaluation of model performance, considering the asymmetry in the dispersion of air pollutants process was conducted through an experiment of traditional convective tank. In this experiment, the countergradient influenced the concentration of pollutants in a convective boundary layer. However, with the parameterizations used, the model failed to capture efficiently the behavior of concentration at points further away from the source.